Also the 4th Dimension of the Town – Its Underground Structures – Has Its Risks - Klouda, Karel; Bradka, Stanislav (Communications - Scientific letters of the University of Zilina, 2008)
The article is devoted to risk assessment of underground structures from the point of view of their existence, operation and human failure (of users and/or operators). Two likely instances of their abuse for disseminating poisonous substances in an urban agglomeration are described. Both possibilities have been scrutinized using either physical simulation or an in-situ experiment. The distribution of agent depending on chosen parameters (agent’s imitation, meteorological conditions, etc.) was verified on Prague’s Old Town Square model in an aerodynamic tunnel. The in situ experiment with surrogates was performed at underground subway changing station. The parameters, results of the experiments and conclusions are discussed in detail.